Pathways from trade to health - Teresa Cyrus (Pan American Health Organization, 2018)
International trade has increased over time, both in volume and as a share of gross domestic product, and international trade agreements have proliferated. This rise in trade has many potential impacts on health outcomes. Trade raises living standards, allowing for greater spending on education and medical care, which improves health. However, trade may worsen intranational inequality, leading to increased stress and adverse impacts on mortality. Labor markets are affected by international trade, and the resulting changes in unemployment, working hours, and injury rates have an impact on health outcomes. Trade may induce adverse environmental impacts, such as increased pollution, leading to worsened health. Reductions in prices as a result of changes to trade policy may increase the consumption of unhealthy goods, including tobacco and processed foods, thus worsening the prevalence of noncommunicable diseases. Trade agreements may affect the ability of governments to legislate health-improving policies. Overall, international trade and trade agreements may have both positive and negative effects on health outcomes; government policy may be used to ameliorate any adverse effects of trade.